PENGARUH HEDONIC SHOPPING MOTIVES, LIFESTYLE,BRAND IMAGE DAN BRAND AWARENESS TERHADAP KEPUTUSAN PEMBELIAN SEPATU VANS (Studi Kasus Pada FEB Unisma Jurusan Manajemen Angkatan 2018) - Etik Ekawati; N Rachma; Budi Wahono (UNIVERSITAS ISLAM MALANG, 2020)
Abstract The research aims to analyse the direct influence and indirect influence of the four variables, namely hedonic shopping motives, lifestyle, brand image and brand awareness of the purchase decision of Vans branded shoes. The population of this research is the management student of 2018 generation. Since it is not known for sure the number of users of Vans shoes in FEB UNISMA Management Force 2018, then samples were taken using Malhotra formula so that obtained 130 respondents qualified as samples. Using multiple linear regression analyses with the analysis tool of SPSS 20The Research was conducted by providing questionnaires and using purposive sampling methods. The results of this study showed that (1) hedonic shopping motives, (2) lifestyle, (3) Brand image and (4) brand awareness are simultaneously influential to the purchase decision, and partially hedonic shopping motives, lifestyle, brand image and brand awareness directly to the purchase decision of Vans shoes. keyword: Hedonic shopping motives, lifestyle, brand image, brand awareness and purchase decision